Aesthetic dominance and expressive influence in a taste for green indoor environment: الهيمنة الجمالية وتأثيرها التعبيري في تذوق البيئة الداخلية الخضراء - Mohammed Jarallah Tewfik, Abdullah Ridha Faisal, Zainab Ali Naser (Journal of engineering sciences and information technology, 2021)
The aesthetic dominance emphasizes sensory pleasure through what is perceived from an aesthetic experience, and this is based on three main elements, Creative designer, design work and recipient, which means that the design work does not express its aesthetic level, as it is not a subject of aesthetic dominance. The aesthetic dominance within the green internal as well as function of expressive influence through symbols. In fact, the moments of aesthetic dominance that we experience are closely intertwined through aesthetic enjoyment, which means that the aesthetic sense is an integral part of our taste for design work. Were it not for this aesthetic feeling, we would not have been able to see the interconnectedness of the multiple parts within the green inner environment. Thus, the aesthetic dominance achieved here means visual beauty that makes the viewer (recipient) spend a pleasant time in this experience as a result of the act of taste based on the aesthetic experience of the interior designer within the green interior environment. The importance of this topic, the problem of this study was formulated with the following question: - What is the role of aesthetic dominance and its expressive effect on the taste of the green internal environment? While the importance of research lies in establishing a theoretical and cognitive base that enriches its scientific material to be of benefit to designers and specialists in the field of interior design and agricultural engineering. In light of this, the goal of the research was determined by revealing the role of aesthetic dominance and its expressive effect in the taste of the green interior environment. While it included the limits of spatial and temporal research study of internal spaces represented by: the building (Eden Project)- England- 2001) and the building (Valley of Butterflies)- Konya- Turkey- 2015). This study will also include the theoretical framework, with defining the topic of the research procedures represented by the research methodology based on descriptive analytical approach (content analysis), while the research community will focus on adopting the intentional selective method, reaching the results of the research study.